Floristic diversity and species composition along altitudinal gradient in the alpine ecosystem of the cold desert region in Western Himalaya, India - Bahukhandi, Amit; Sekar, K. Chandra; Negi, Vikram S.; Bisht, Kapil; Tiwari, Deep C.; Mehta, Poonam; Upadhyay, Shashi; Siddiqui, Sazada; Ayari-Akkari, Amel (Frontiers in Plant Science, 2024)
In India, the Trans-Himalayan zone lies in the rain shadow of the main Himalayan region and is usually described as a ‘high altitude cold desert’. These regions are represented by sparse, but unique vegetation composition. The present study is an attempt to investigate the vegetation composition in the alpine ecosystem of the cold desert landscape that is Nelang Valley in western Himalaya (Uttarakhand), India. The result of the study reveals the existence of a total of 68 taxa of higher plants (56 genera and 28 families). These include herbs (51 species), shrubs (13 species), climbers (1 species), and tree species (3). Herbaceous species (52 species) contributed the maximum in species richness; Artemisia, Astragalus, and Juniperus were the dominant genera followed by Aster, Lonicera, Oxytropis, Poa, and Salix. The valley showed irregular distribution of plant species richness along the altitudinal gradient, and maximum taxa exhibited between 3500-3600 m altitude band. In the Nelang Valley, the total number of phytodiversity individuals exhibited a significant linear decline with increasing altitude (3100-4300 m). Further, the study recorded 33 important medicinal plants used in the traditional system of herbal medicine in the Himalayan region. Juniperus semiglobosa shows dominance with maximum IVI (31.77) followed by Pinus wallichiana (29.19) and Cedrus deodara (10.72 in the treeline ecotone of the Valley. Rapid Threat Assessment shows that Artemisia dubia and A.roxburghiana were found most vulnerable herb species in the region. The information thus generated will be useful for suggesting ecological management and conservation planning.